Analisis Perancangan Pipa Gas Buang Diesel Generator Pada Konversi Kapal Chemical Tanker 6200 DWT menjadi PLTD Terapung - Della Al Bilatri Wahyu S; George Endri Kusuma; Pekik Mahardhika (Politeknik Perkapalan Negeri Surabaya, 2023)
- The construction of the Floating Diesel Power Plant (PLTD) is one of the government'sefforts to overcome an uneven distribution of electrical energy in Indonesia. The Floating PLTD is aconversion of a 6200 DWT chemical tanker with 2 main engines into 6 Wartsila 12V32 dieselgenerators as power plants. Due to the conversion, several new piping systems are needed withlimited space due to the dimensions of the ship. This research focuses on planning the exhaust gaspiping system of each diesel generator. Planning includes pipe routing, insulator thicknessdetermination, back pressure and pipe stress analysis. Based on manual and software calculations,the insulator thickness used is 40 mm with an efficiency of 68% to 94%. The results of back pressureanalysis in each design using the Darcy-Weisbach method and software show an eror of 4,36% to13,15% with an average back pressure below the maximum limit of 4.246 kPa. The results of the pipestress analysis show that the ratio between the stress value that occurs and the maximum allowablevalue is less than 1, with an average stress due to fixed load of 0,065, stress due to thermal load of0,787, and hoop stress of 0,058. Based on the results of the back pressure and pipe stress analysis,the design is acceptable and safety.